Optimizing Recruitment Process, Candidate and Employee Data at MAP Active - Claraficia Renata Utoyo; Denta Felli Ananda; Aulia Danibrata; Erika Jimena Arilyn (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2023)
The MBKM program aims to provide opportunities for students to learn about the work environment directly and develop their abilities. As HR – Recruitment intern, the author is responsible for assisting the recruitment process, managing candidate and employee data at MAP Active. In addition, the author also created a project entitled DarwinBox Recruitment Guidebook as a tool to assist the recruitment process. Overall, the MBKM program has effectively and efficiently helped develop the self-qualities of the participants. The MBKM program makes a positive contribution to participants, companies and society.